Availability, Accessibility, and Teachers’ Utilization of Science Laboratory Resources in Public Secondary Schools of Ilocos Norte - Cabusor, Sheila Marieh; Antonio, Vida V. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
Access to basic educational facilities is vital for creating an ideal learning environment. The establishment of science laboratories provides educators with essential resources to expound abstract scientific concepts, hence, improving student understanding. This study intended to assess the availability and level of utilization of science laboratory resources in Public Secondary Schools of Ilocos Norte. The study followed descriptive research methodology and purposive sampling to collect data from 198 Junior and Senior High School Science teachers. The instruments used for the study was adapted from DO # 17, s. 2017, and DO # 42, s. 2006. The results of the study indicated that in most participating schools; basic science laboratory apparatuses are highly available. However, majority of the schools are highly inadequate with advanced laboratory apparatus and laboratory chemicals. Moreover, this study revealed that most schools do not have their separate dark rooms and shower rooms. In terms of level of utilization, there is no apparatus that is Always utilized, and dark room is Never utilized. The study recommended for a nationwide or regional survey of schools to evaluate the availability of science laboratory resources and correlate this information with student performance indicators. The researchers suggest on analysing current policies on scientific education funding and resource allocation that would targets areas for enhancement and promote equal distribution of resources. These will enable the establishment of adequate science laboratories and resources in all schools to enhance the effective teaching and learning of science.